Administrasi dan Sistem Pendidikan Di Negara Maju Finlandia dan Mesir - Putri, Lidia; Rouf, Assa Dullah; Dafirsam, Dafirsam; Ilmi, Darul (Universitas Pahlawan Tuanku Tambusai, 2023)
Administration is an activity that occupies a major position in providing training and developing all cooperation activities of a group of people, and there must also be an organization that can provide development and achieve the goals of education in the field of education. Finland implemented peruskoulu, a new system of education designed to correct many of the problems created by the corresponding system. Finland has embodied an education system with consistent features, such as free education, free school meals, and special needs education, while adhering to the principle of inclusivity. Islamic education has a long history. In the field of social history, the Prophet Muhammad, who became the disseminator of God's commandments, was born in a region with a culture that was hard to change.